2013
DOI: 10.1007/978-3-642-38007-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: From Basic Studies to Bedside

Abstract: Plants produce a remarkable amount of low molecular mass natural products endowed with a large array of pivotal biological activities. Among these molecules, resveratrol (3,5,4'-trihydroxystilbene) has been identified as an important modulator of cell phenotype with a complex and pleiotropic mode of action. Extensive literature regarding its activity, mainly employing cellular models, suggests that this polyphenol controls cell proliferation, induces differentiation, and activates apoptosis and autophagy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 109 publications
0
40
0
3
Order By: Relevance
“…Accumulating evidence regarding its activity reveals that Res has an effect on cell proliferation, differentiation, apoptosis and autophagy (4,5). Furthermore, it has been demonstrated that Res has a suppressive effect on various types of human malignancy (6).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence regarding its activity reveals that Res has an effect on cell proliferation, differentiation, apoptosis and autophagy (4,5). Furthermore, it has been demonstrated that Res has a suppressive effect on various types of human malignancy (6).…”
Section: Introductionmentioning
confidence: 99%
“…(e.g. resveratrol [160]). Phytoestrogens stimulate estrogen receptors, alpha and beta and many are endowed with antioxidant, and pro-apoptotic effects [161], while some may also have pro-or anti-angiogenic effects [162].…”
Section: Persistent Organic Pollutants (Pop) and Polycyclic Aromatic mentioning
confidence: 99%
“…Res has extensive pharmacological effects, including anticancer properties (14)(15)(16)(17), improving ifosfamide-induced Fanconi syndrome in rats (18), treating diabetic nephropathy (19) and neuronal protection (20,21). Though previous studies have suggested that Res has an anti-inflammatory effect, the role of Res in mediating inflammation remains to be understood (22). The present study aims to investigate the role of the TLR4/NF-κB signaling pathway in the anti-inflammatory effect of Res in a rat model of MI/R.…”
Section: Introductionmentioning
confidence: 98%